Social and Cultural Dynamics in the Interactions Among Students at the Qur’anic Center Islamic Boarding School Tulang Bawang Barat - Risa Khafifatur Rohmah; Siti Roudhotul Jannah; M. Zaenal Arifin (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
Differences in ethnicity, language, religion, and socioeconomic status can serve as sources of strength but also present challenges in building social unity. In recent years, increasing polarization, the rise of identity-based conflicts, and the decline of communal values indicate that social integration does not always occur harmoniously. In this context, Islamic boarding schools (pesantren) function not only as religious educational institutions but also as social spaces that reflect the diversity of community life, where students from different backgrounds live together and engage in intensive daily interactions. This study employs a qualitative approach with a case study design. Data collection techniques include observation, in-depth interviews, and documentation, with informants selected using purposive sampling. Data were analyzed inductively through reduction, presentation, and conclusion drawing. This study aims to describe the social and cultural dynamics in student interactions and to analyze the functional relationship between the two in creating harmonious interactions within the pesantren environment. The scope of the study focuses on students' social interaction patterns, cultural adaptation processes, and the role of pesantren values in shaping solidarity and conflict resolution. The findings indicate that the social and cultural dynamics among students occur through adaptation, internalization of pesantren values, and cultural acculturation, which foster cross-cultural solidarity (ukhuwah), while also contributing to the character development of students with Qur’anic morals